Clinico-therapeutic study of pyodemodicosis with underlying ulcerative keratitis: A Case report - Gupta, Kapil Kumar; Kaur, Jasleen; Singh , Gagandeep; Mahajan, Chetna (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Six month old male pug was presented in veterinary clinical complex, college of veterinary science, Rampura Phul with the anamnesis of inappetence, chronic corticosteroid and antihistaminic therapy and clinical signs of generalized alopecia, erythema, mild itching, pustular dermatitis, corneal edema and ulcerative keratitis. Microscopic examination of deep skin scrapings revealed presence of Demodex canis mites. Hepatorenal biomarkers and electrolyte parameters were analyzed and revealed no significant change. Therapeutic management was started with oral fluralaner, cephalexin and topical antimicrobial shampoo. For ophthalmic infection 5% w/v sodium chloride, Tobramycin, fresh extract of human placenta and autologous serum were applied topically. Clinical and parasitological cure were seen after 56 days post therapy and three consecutive negative skin scrapings were obtained in order to confirm the absence of disease.
Keywords: Clinico-Therapeutic; Pyodemodicosis; Underlying